Regional differences in the frequency of the c.985A>G ACADM mutation: findings from a meta‐regression of genotyping and screening studies. (3rd May 2013) - Leal, J.; Ades, A.E.; Wordsworth, S.; Dezateux, C.
<x xml:space="preserve">Abstract</x> Several countries include medium‐chain acyl‐CoA dehydrogenase (MCAD) deficiency, a rare autosomal recessive disease, in their newborn screening programmes despite prevalence uncertainty. We estimated the frequency of its most common mutation, c.985A>G, tested for regional differences and compared screening and genotype frequencies. We identified 43 studies reporting the frequency of c.985A>G over 10 million individuals, and pooled frequency data using a novel Bayesian approach. We found significant variation in the frequency of the mutation across regions supporting a reported founder effect. The proportion of c.985A>G homozygotes was highest in Western Europe with 4.1 (95%CI: 2.8–5.6) per 100, 000 individuals, then the New World (3.2, 95%CI: 2.0–4.7), Southern (1.2, 95%CI: 0.6–2.0) and Eastern European regions (0.9, 95%CI: 0.5–1.7). No cases with the mutation were identified in Asian and Middle Eastern regions. Significant differences were found in some countries between the genotype and screening allele frequency of c.985A>G. Our predictions could inform the frequency of the mutation by region and our approach could apply to other genetic conditions.